DETERMINAN STRUKTUR MODAL BANK - Nurshadrina Kartika Sari; Isti Fadah; Hari Sukarno (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2013)
Banks are financial institutions how have an important part for the economy of a country. The bank’s main purposes are to collected funds from the public and distributed it back to them in credit loans. The biggest of public trusted to the bank, will make the bigger bank’s liabilities to their funds. This research examines determinants of bank capital structure, including profitability, liquidity, business risk, dividend, management ownership, institutional ownership and bank’s age. The samples in this research are 70 banks in Indonesian period 2006 until 2011, where analyzed with multiple linier regression test with dummy variable to know which of the seven variables are the determinans of the bank capital structures that use DER (Debt to Equity Ratio) to measure it. The result of this research find that determinants of bank capital structures is liquidity, institutional ownership and bank’s age, but profitability, business risk, dividend and management ownership are not the determinants of bank capital structures period 2006 until 2011